2016
DOI: 10.1111/bph.13442
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic, release‐regulating mGlu2‐preferring and mGlu3‐preferring autoreceptors in CNS: pharmacological profiles and functional roles in demyelinating disease

Abstract: BACKGROUND AND PURPOSEPresynaptic, release-regulating metabotropic glutamate 2 and 3 (mGlu 2/3 ) autoreceptors exist in the CNS. They represent suitable targets for therapeutic approaches to central diseases that are typified by hyperglutamatergicity. The availability of specific ligands able to differentiate between mGlu 2 and mGlu 3 subunits allows us to further characterize these autoreceptors. In this study we investigated the pharmacological profile of mGlu 2/3 receptors in selected CNS regions and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 62 publications
(81 reference statements)
3
37
0
Order By: Relevance
“…Experiments were carried out to quantify the effects of antagonists alone and of pretreatment of the synaptosomes with antibodies on the KCl‐evoked release of [ 3 H]‐D‐Asp. In accord with our previous results (Di Prisco et al, ) and consistent with Curtis et al . (), at least n = 5 replicates were carried out for each experimental condition.…”
Section: Methodssupporting
confidence: 94%
See 3 more Smart Citations
“…Experiments were carried out to quantify the effects of antagonists alone and of pretreatment of the synaptosomes with antibodies on the KCl‐evoked release of [ 3 H]‐D‐Asp. In accord with our previous results (Di Prisco et al, ) and consistent with Curtis et al . (), at least n = 5 replicates were carried out for each experimental condition.…”
Section: Methodssupporting
confidence: 94%
“…The recent discovery of new ligands able to separate the role of the two receptors has allowed the pharmacological characterization of the native mGlu 2/3 receptors. Consistently, we recently proposed the existence of presynaptic mGlu 3 ‐preferring autoreceptors in spinal cord glutamate terminals and presynaptic mGlu 2 ‐preferring autoreceptors in the cortex of adult mice (Di Prisco et al, ). These conclusions originated from the results obtained in release studies with N‐acetyl‐aspartyl‐glutamate (NAAG), which has been shown to selectively activate the mGlu 3 receptor subtype (Neale et al, ; Romei et al, ; Di Prisco et al, ) and LY541850, a selective mGlu 2 receptor agonist with mGlu 3 receptor antagonist activity (Hanna et al, ; Sanger et al, ).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…It is the case of the double-faced mGlu2/3 ligand the compound LY541850, which activates mGlu2 receptor subtypes but inhibits mGlu3 receptors (Di Prisco et al, 2016). …”
Section: The Up–down Superfusion Of a Thin Layer Of Synaptosomes: Sommentioning
confidence: 99%